Effect of algae extract and Bio-fertilizer on vegetative growth and flowering of Freesia hybrid L. - Kadhim, Zaid Khaleel; AL-Shareefi, Mohammed; Hakim, Rabab A. M. (Journal of Kerbala for Agricultural Sciences, 2019)
Abstract The present investigation was aimed to find out the effect of foliar application of algae extract and Bio-fertilizer on growth and flowering yield of Freesia plant. , which was carried out in winter 2018 at experimental site of Department of Horticulture, Faculty of Agriculture. The experiment was laid out in randomized complete block design (R.C.B.D) with three replications and two factors. The first factor consisted 2 levels of algae extract foliar spray ( Zero, 3) ml/L, coded as A0, A1 the treatments were applied three times ( 15 , 30 , 45 ) after germination, and the second one involved 2 levels of Bio-fertilizer (Zero,10 ) g/L, coded as B0, B1 The treatments were applied after 10 days of germination. These studies find the significant effect of algae extract with Bio-fertilizer on vegetative growth and flowering yield. The treatment (A1B1) recorded higher average in the Plant height. While The treatment (A1B0) gave higher average in the number of leaves per plant, chlorophyll content, length flowering stem, number of inflorescences plant, number of florets inflorescence, but there were no a significant difference with the treatment (A1B1).